The Problem with Crime Problem-Solving: Towards a Second Generation Pop?. (22nd May 2019) - Borrion, Hervé; Ekblom, Paul; Alrajeh, Dalal; Borrion, Aiduan Li; Keane, Aidan; Koch, Daniel; Mitchener-Nissen, Timothy; Toubaline, Sonia
Abstract: In his 2018 Stockholm prize winner lecture, Goldstein highlighted the need for problem-oriented policing (POP) to be not only effective but also fair. Contributing to the development of POP, this study examines how a wider perspective on problem-solving generally, and scoping in particular, can be adopted to address some of the growing challenges in 21st century policing. We demonstrate that the concept of 'problem' was too narrowly defined and that, as a result, many problem-solving models found in criminology are ill-structured to minimize the negative side-effects of interventions and deliver broader benefits. Problem-solving concepts and models are compared across disciplines and recommendations are made to improve POP, drawing on examples in architecture, conservation science, industrial ecology and ethics.